PENERAPAN MODEL PEMBELAJARAN CORE UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KESETIMBANGAN ION DAN pH LARUTAN GARAM - Nesa Nozari; Herdini Herdini; Asmadi M. Noer (Jurnal Pendidikan Kimia Universitas Riau, 2020)
The research aims to improve student learning results on ion equilibrium and pH of salt solution in class XI IPA SMAN 6 Pekanbaru. This is an experimental study with a pretest-posttest design. The sample study was students of class XI IPA 2 as an experimental class and students in class XI IPA 1 as a control class. The experimental class is the class applied to the CORE learning model while the control class is not treated. The data analysis technique used is the t-test. Based on the results of the data analysis test, tcount> ttable is 9,03> 1.66, meaning that the application of CORE’s learning model can improve student learning achievement on the subject of ion equilibrium and pH of salt solution in class XI IPA 6 SMAN 6 Pekanbaru